The cost of seeing the meaning: Conceptual processing of distractors triggers localized target suppression. Issue 9 (25th November 2016) - Wang, Lingling; Most, Steven B.
ABSTRACT: It is often assumed that conceptual information impacts visual experience only after perceptual information has been extracted. However, the present study suggests that conceptual processing can interfere with perceptual processes, as reflected in target perception impairments that are specific to the location of conceptually salient distractors. Experiment 1 replicated previous findings that emotional distractors in a rapid serial visual presentation cause a spontaneous, spatially localized impairment in target perception, further finding that distractors that are merely featurally salient do not. Experiment 2 suggested that conceptually salient distractors that are non-emotional also elicit such spatially localized impairments, which are shorter lived than those following emotional distractors. Experiment 3 suggested that featurally salient distractors that are not conceptually salient engage a different, spatial attention mechanism. Together, these findings suggest that, whereas featurally salient distractors can capture spatial attention, conceptual distractors additionally engage mechanisms that suppress spatiotemporally competing targets.